The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3389/fnhum.2021.674139
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Visual Stimulation-Induced Passive Reproduction of Motor Images in the Brain on Motor Paralysis After Stroke

Abstract: Finger flexor spasticity, which is commonly observed among patients with stroke, disrupts finger extension movement, consequently influencing not only upper limb function in daily life but also the outcomes of upper limb therapeutic exercise. Kinesthetic illusion induced by visual stimulation (KINVIS) has been proposed as a potential treatment for spasticity in patients with stroke. However, it remains unclear whether KINVIS intervention alone could improve finger flexor spasticity and finger extension movemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Recent research has demonstrated that visual–motor illusion (VMI) can elicit kinesthetic sensations through visual stimulation [ 9 , 10 , 11 ]. VMI employs a video image displayed on a monitor to mimic limb motion, creating the illusion that the patient’s limbs are in motion, even though they are not physically moving [ 12 , 13 , 14 , 15 , 16 , 17 ]. Similarly, as another intervention that uses illusions, the effectiveness of mirror therapy has been reported [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has demonstrated that visual–motor illusion (VMI) can elicit kinesthetic sensations through visual stimulation [ 9 , 10 , 11 ]. VMI employs a video image displayed on a monitor to mimic limb motion, creating the illusion that the patient’s limbs are in motion, even though they are not physically moving [ 12 , 13 , 14 , 15 , 16 , 17 ]. Similarly, as another intervention that uses illusions, the effectiveness of mirror therapy has been reported [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Visual stimulation plays an important role in increasing neurological stimulation and increasing the range of motion of post stroke patients. Interventions given through visual stimulation for 20 minutes can increase muscle flexibility and reduce muscle spasticity in 70.1% of stroke patients (Aoyama et al, 2021). One of the visual stimulation that is currently mostly done using virtual reality technology.…”
mentioning
confidence: 99%